Geographical origins of language structures - Oded Galor; Ömer Özak; Assaf Sarid (Brown University, Department of Economics, 2018)
This research explores the geographical origins of the coevolution of cultural and linguistic traits in the course of human history, relating the geographical roots of long-term orientation to the structure of the future tense, the agricultural determinants of gender bias to the presence of sex-based grammatical gender, and the ecological origins of hierarchical orientation to the existence of politeness distinctions. The study advances the hypothesis and establishes empirically that: (i) variations in geographical characteristics that were conducive to higher natural return to agricultural investment contributed to the existing cross-language variations in the structure of the future tense, (ii) the agricultural determinants of gender gap in agricultural productivity fostered the existence of sex-based grammatical gender, and (iii) the ecological origins of hierarchical societies triggered the emergence of politeness distinctions.
Keywords: D01; D03; J16; Z10; Z13; 330; Comparative Development; Cultural Evolution; Language Structure; Future Tense; Politeness Distinctions; Long-Term Orientation; Grammatical Gender; Gender Bias; Hierarchy; Emergence of States; Entwicklung; Räumliche Verteilung; Linguistik; Sozialer Wandel; Evolutionsökonomik; Agrargeschichte; Agrargeographie; Ernteertrag; Welt